Photonic Bandgap Closure and Metamaterial Behavior in 1D Periodic Chains of High-Index Nanobricks - Evelyn Díaz-Escobar; Laura Mercadé; Ángela I. Barreda; Jaime García-Rupérez; Alejandro Martínez (Photonics, 2022)
It has been shown that the photonic bandgap of one-dimensional (1D) dielectric periodic thin films can vanish at the first Bragg condition for TM modes. Here, we address the case of 1D photonic crystal slabs formed by a chain of high-index dielectric particles with transversal confinement and show that the Bragg bandgap can vanish for both TE- and TM-like modes. Calculations using plane-wave expansion and finite-difference time-domain methods confirm that the PBG vanishes. PBG closure is explained as being a result of the interplay between the electric and magnetic dipole resonances of the isolated nanoparticle with Bragg resonance, as confirmed by calculating the electric and magnetic dipoles of the isolated nanobricks. This can be considered as a manifestation of the metamaterial behavior of the 1D system when using silicon as an underlying material. Our finding may have important consequences for the fields of photonic crystals and all-dielectric metamaterials.